Content Delivery in Vehicular Ad Hoc Networks - Silva, Fabrício A.; Ruiz, Linnyer B.; Loureiro, Antonio A. F. (Anais do Concurso de Teses e Dissertações da SBC (CTD-SBC), 2016)
Vehicular Ad Hoc Network (VANET) applications are emerging to reality with the objective of making traffic safer, less congested, more informative, and enjoyable. With the advance of such applications, comes the need for content delivery solutions, since the efficient delivery of content is a fundamental requirement for most vehicular network applications. The main objective of this thesis is to investigate how existing concepts can be adapted and applied to VANETs and to propose content delivery solutions for this kind of network.